Conjunctival melanoma: New insights in tumour genetics and immunology, leading to new therapeutic options. (January 2022) - Brouwer, Niels J.; Verdijk, Robert M.; Heegaard, Steffen; Marinkovic, Marina; Esmaeli, Bita; Jager, Martine J.
Abstract: Recent developments in oncology have led to a better molecular and cellular understanding of cancer, and the introduction of novel therapies. Conjunctival melanoma (CoM) is a rare but potentially devastating disease. A better understanding of CoM, leading to the development of novel therapies, is urgently needed. CoM is characterized by mutations that have also been identified in cutaneous melanoma, e.g. in BRAF, NRAS and TERT . These mutations are distinct from the mutations found in uveal melanoma (UM), affecting genes such as GNAQ, GNA11, and BAP1 . Targeted therapies that are successful in cutaneous melanoma may therefore be useful in CoM. A recent breakthrough in the treatment of patients with metastatic cutaneous melanoma was the development of immunotherapy. While immunotherapy is currently sparsely effective in intraocular tumours such as UM, the similarities between CoM and cutaneous melanoma (including in their immunological tumour micro environment) provide hope for the application of immunotherapy in CoM, and preliminary clinical data are indeed emerging to support this use. This review aims to provide a comprehensive overview of the current knowledge regarding CoM, with a focus on the genetic and immunologic understanding. We elaborate on the distinct position of CoM in contrast to other types of melanoma, and explain how new insights in the pathophysiology of this disease guide the development of new, personalized, treatments. Highlights: CoM is a rare but potentially deadly extraocular tumour, with a rising incidence. Genetic mutations in CoM resemble those in cutaneous melanoma, but not UM. The presence of immune cells is important for the development and control of CoM. Targeted therapy and checkpoint inhibitors can be applied to treat CoM patients.